Judicial and Legal Reform as an Element of Implementation of the EU-Ukraine Association Agreement in the Field of Justice - Mykiievych, Mykhailo; Ivanochko, Iryna (Teisė, 2020)
The article considers distinctive features of the judicial and legal reform in Ukraine in the context of European integration processes, determines the key elements of the institutional mechanism in the implementation of the EU–Ukraine Association Agreement, outlines the main achievements and prospects in the reform of the judiciary in Ukraine.